Programming with Microsoft Visual Basic 6.0 - Zak, Diane
Designed for an introductory programming course, this market-leading title has been enhanced to include two new tutorials on the next generation of Visual Basic - Visual Basic.NET. Programming with Visual Basic 6.0 Enhanced distinguishes itself from other Windows books because of its unique two-pronged approach. First, this book teaches programming concepts using a task-driven, rather than a command-driven, approach. By working through the tutorials, which are each motivated by a realistic case, individuals learn how to use programming applications that they are likely to encounter in the workplace. Second, the content, organization, and pedagogy of this book exploits the Windows environment. This edition includes creating reports using the print statement, as well as two full chapters on database access using ADO data control, SQL, and the DBGrid control